Bibliometric Analysis of Community Nursing Trends on the Role of Nurses in Community Health Improvement - Yanuaria Buka, Sisilia prima; Ramdhani, Rahmat; Andarmoyo, Sulistyo (West Science Interdisciplinary Studies, 2024)
This study employs bibliometric analysis using VOSviewer to map the landscape of health promotion research from 2004 to 2014. By analyzing research publications in this field, we identify thematic clusters, research trends, and emerging opportunities for future investigations. Our analysis reveals several thematic clusters central to health promotion, including health education, empowerment, community engagement, and the role of healthcare professionals. A temporal analysis of the research trends indicates a shift in focus from basic educational and community engagement strategies to more specialized areas, with a notable increase in research on mental health towards the end of the period studied. The examination of less illuminated areas within the network visualization highlights underexplored topics such as the roles of community pharmacists and integrative reviews, suggesting them as potential rich fields for future research. The study underscores the evolution of health promotion over the decade and points to new directions for comprehensive health strategies, aiming to bridge research gaps and foster interdisciplinary collaboration.